A Model Integrating Islamic Religiosity and Theory of Planned Behavior to Explain the Dynamics of Halal Consumption Behaviors - Abdul Khalek, Aiedah; Syed Ismail al-Qudsy, Sharifah Hayaati; Mohamad Ibrahim, Hairunnisa (Online Journal of Research in Islamic Studies, 2023)
Halal is a fundamental Islamic principle that generally shapes Muslim consumption behaviours. Even though the halal concept originates from religious sources, limited studies found focusing on the role of religiosity in investigating halal consumption behaviors. The Theory of Planned Behaviour (TPB) has been widely used to predict the behavioural intention of halal consumption behaviours among Muslims. This study aims to extend the discourse by integrating the religiosity construct in the TPB in which we examine the influence of religiosity as an additional variable to the other main determinants of behavioural intentions as theorized in the TPB. This is a cross-sectional study conducted among millennials Muslims who frequently eat out in the urban areas of Klang Valley, Malaysia. The findings reveal that religiosity has the strongest influence to determine halal food consumption compared to other determinants as outlined in the TPB. The proposed integration of religiosity variables in the TPB model contributes to extending literature in halal consumption as well as providing analysis on the role of religiosity in propelling the halal consumption behavior. Hence, this paper offers theoretical underpinnings and empirical evidence for this discourse.